OP0031 ARE THE MODIFIED NEW YORK AND ASAS AXIAL SPONDYLOARTHRITIS CRITERIA INTERCHANGEABLE IN THE CLASSIFICATION OF SPONDYLOARTHRITIS PATIENTS WITH RADIOGRAPHIC SACROILIITIS: COMPARISON IN 8 COHORTS?. (June 2019) - Boel, Anne; Moltó, Anna; Heijde, Désirée van der; Ciurea, Adrian; Dougados, Maxime; Gensler, Lianne S.; Santos, Maria Jose; Miguel, Eugenio de; Poddubnyy, Denis; Rudwaleit, Martin; Tubergen, Astrid van; van Gaalen, Floris A.; et al.
Abstract : Background: Axial spondyloarthritis (axSpA) patients with radiographic sacroiliitis may be classified using the modified New York (mNY) criteria) and the more recent ASAS criteria. In the mNY criteria these patients are referred to as ankylosing spondylitis (AS) patients and in the ASAS criteria as radiographic axSpA (r-axSpA) patients. In both the mNY and the ASAS r–axSpA classification sets the radiographic criterion is the same but the additionally required features differ (figure), for example patients with age at onset of back pain ≥45 cannot fulfil the ASAS criteria. This raises the question whether the two sets can be used interchangeably in the classification of axSpA patients with radiographic sacroiliitis. Objectives: To investigate to what degree patients with axSpA and radiographic sacroiliitis who fulfil the mNY criteria also fulfil the ASAS criteria for r–axSpA and vice–versa. Methods: Patients diagnosed with axSpA who had back pain longer than 3 months and definite radiographic sacroiliitis (i.e. common and mandatory features for both classification criteria sets (figure)) were selected from several cohorts (ASAS, Esperanza, GESPIC, OASIS, Reuma.pt, SCQM, SPACE, and UCSF). Subsequently we calculated how many patients fulfil the mNY criteria and/or the ASAS r–axSpA criteria. For the Esperanza and OASIS cohorts specific information on the individual items of the mNY criteria was unavailable, which restricted data analysis for these cohorts. Results: Of the 3882 patients fulfilling the mNY criteria, 93% also fulfilled the ASAS r–axSpA criteria. Inversely, of the 3434 patients fulfilling the ASAS r–axSpA criteria, 96% also fulfilled the mNY criteria (table). In total, 89% (3607/4041) of patients with axSpA and radiographic sacroiliitis fulfilled both criteria sets; 7% only the mNY criteria; 3% only the ASAS criteria and 1% neither set. The main difference between the two criteria sets was caused by reported age at onset of back pain. Out of 275 mNY+ patients not fulfilling the ASAS criteria (7% of all included patients), 265 (96%) cases were due to the age criterion and 10 (4%) due to the absence of SpA features. Of the 3434 ASAS+ patients, 90% fulfilled the mNY criteria because they had IBP, another 6% despite not having IBP fulfilled the mNY criteria due to a mobility restriction; and the remainder 4% had neither but fulfilled the ASAS criteria because of other SpA features. Conclusion: AxSpA patients classified as AS according to mNY criteria and those classified as r–axSpA according to ASAS criteria are mostly the same: 93% of mNY positive patients also fulfil the ASAS r-axSpA criteria while 96% of ASAS r–axSpA positive patients also fulfil the mNY criteria. These findings support the interchangeable use of the terms r–axSpA and AS, which was also approved by a vote of ASAS members at the 2019 annual workshop in Amsterdam. Disclosure of Interests: Anne Boel: None declared, Anna Moltó: None declared, Désirée van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Daiichi, Eli-Lilly, Galapagos, Gilead, GlaxoSmithKline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, Union Chimique Belge, Adrian Ciurea Consultant for: AbbVie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, maxime dougados Grant/research support from: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma, Consultant for: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma, Lianne S. Gensler Grant/research support from: Abbvie, Amgen, UCB Pharma, Consultant for: Novartis, Lilly, Janssen, Maria Jose Santos: None declared, Eugenio de Miguel: None declared, Denis Poddubnyy Grant/research support from: AbbVie, Merck Sharp & Dohme, Novartis, Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, UCB Pharma, Speakers bureau: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Roche, UCB Pharma, Martin Rudwaleit Consultant for: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma, Consultant for: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma, Astrid van Tubergen: None declared, Floris A. van Gaalen: None declared, Sofia Ramiro Grant/research support from: MSD, Consultant for: AbbVie, Lilly, MSD, Novartis, Pfizer, Sanofi, Speakers bureau: AbbVie, Lilly, MSD, Novartis, Pfizer, Sanofi